2017
DOI: 10.3130/jaabe.16.395
|View full text |Cite
|
Sign up to set email alerts
|

Pile Foundation Design Through the Increased Bearing Capacity of Extended End Pile

Abstract: Pretensioned spun high strength concrete (PHC) piles are a commonly used type of pile, while approximately 60% of the pile's strength is only used in the design bearing capacity. Because of the limited support capacities of PHC piles, applying PHC piles to high-rise buildings or soft ground is inefficient. Extended end (EXT) piles are a new type of pile that can reduce the waste of pile strength and increase the ground bearing capacity. This study investigated the behavior of EXT piles through a field test and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…As a common form of deep foundation, high pile foundation is widely used in complex and difficult projects such as wharves, cross-sea Bridges, and viaducts of high-speed railway lines in Marine environments due to its good seismic performance, strong adaptability, and high bearing capacity [1]. The ratio of length to slenderness of a high pile foundation is much larger than that of a short, rigid pile, which is more prone to instability or large deformation under the action of a dynamic load, thus leading to the destruction of the pile foundation and superstructure.…”
Section: Introductionmentioning
confidence: 99%
“…As a common form of deep foundation, high pile foundation is widely used in complex and difficult projects such as wharves, cross-sea Bridges, and viaducts of high-speed railway lines in Marine environments due to its good seismic performance, strong adaptability, and high bearing capacity [1]. The ratio of length to slenderness of a high pile foundation is much larger than that of a short, rigid pile, which is more prone to instability or large deformation under the action of a dynamic load, thus leading to the destruction of the pile foundation and superstructure.…”
Section: Introductionmentioning
confidence: 99%
“…Nguyen et al used feedforward neural network (FFN) to study the ultimate axial bearing capacity of PHC node piles [2]. Kim et al investigated the performance of Extended end (EXT) piles by field tests and confirmed that the bearing capacity of EXT piles is better than PHC piles [19]. Huynh et al developed a new direct SPT method using a genetic algorithm with function optimization, which can accurately predict the ultimate axial bearing capacity of PHC ball piles [20].…”
Section: Introductionmentioning
confidence: 99%
“…The predicted ultimate bearing capacity results were verified through the static load test results of PRBS in historical cases, indicating that the finite element cavity expansion method is accurate and reliable. Kim [ 15 , 16 ] tested and analyzed the PHC pipe piles and EXT piles widely used in South Korea, and the results showed that compared with PHC piles, EXT piles with welded ring steel plates at the end increased the vertical bearing capacity by more than 20%, and could shorten the construction period and reduce the project cost. Gao [ 17 ] conducted a test study on 16 large-diameter hand-dug pile with enlarged bottom, and the results showed that increasing the diameter of enlarged bottom had a more significant effect on improving the bearing capacity than increasing the pile diameter.…”
Section: Introductionmentioning
confidence: 99%